Kinetics and function of peritoneal-exudate cells during local IL-2 gene-therapy of cancer - Bubenik, J; Zeuthen, J; Indrova, M; Bubenikova, D; Simova, J (International journal of oncology, 1994)
The present study was designed to examine the kinetics and function of peritoneal exudate cells (PEC) during local interleukin 2 (IL-2) gene therapy of the X63-Ag8.653 plasmacytoma growing in the peritoneal cavity. BALB/c mice were inoculated i.p. on day 0 with a tumorigenic dose of the syngeneic plasmacytoma and on day 1 with non-tumorigenic plasmacytoma cells carrying an inserted IL-2 gene and producing constitutively IL-2. At regular time intervals the experimental mice were sacrificed and their peritoneal exudate cells were used for phenotypic analysis and Cr-51 microcytotoxicity assay. On the first day after i.p. inoculation of the genetically modified plasmacytoma cells the percentage of Thy 1.2+, CD3+, TCR alphabeta+ T lymphocytes and NK+ cells in the peritoneal fluid dramatically increased. The levels of the positive cells continually decreased until day 11, when the values of normal, healthy mice were obtained. The percentage of Thy 1.2+ and CD3+ cells remained at these, or slightly lower values, until the end of the observation period. A similar, though more slowly descending kinetics was seen in the CD5+ cell population, whereas the CD8+ cells, compared to the controls, exhibited only a short-term peak between days 3 and 5, and the values of TCR alphabeta+ and NK+ cells exhibited a second peak between days 25 and 48. The percentage of TCR gammadelta+ cells showed a permanent, moderately elevated plateau from day 1 till the end of the observation period. In control, untreated mice, inoculated i.p. with the X63-Ag8.653 plasmacytoma, the kinetics of peritoneal exudate cells was different. A moderate, permanent elevation of all of the T and NK cell subsets examined occured during the observation period. In addition, the percentage of TCR alphabeta+, TCR gammadelta+ and NK+ cells further increased continually from day 11 till the end of the observation period. The cytolytic activity of the peritoneal exudate cells was examined in vitro concurrently with FACS phenotyping. Free tumour-specific killer cells generated in the peritoneal fluid due to the local IL-2 gene therapy were found only on day 6, and these cells were cytolytic for both, the parental X63-Ag8.653 and the genetically modified X63-m-IL-2 plasmacytoma cells.